Poly(ε-benzyloxycarbonyl-L-lysine)-grafted branched polyethylenimine as efficient nanocarriers for indomethacin with enhanced oral bioavailability and anti-inflammatory efficacy. (February 2017) - Lu, Chao; Li, Xin; Xia, Wenquan; Lu, Siheng; Luo, Hongjun; Ye, Danyan; Zhang, Yanmei; Liu, Daojun
Graphical abstract: Abstract: Star-block copolymers PEI -g- PZLL with a branched polyethylenimine (PEI) core and multiple grafted poly(ε-benzyloxycarbonyl-L -lysine) (PZLL) peripheral chains were designed, synthesized, and evaluated as nanocarriers for indomethacin (IND). In an aqueous solution, PEI -g- PZLL self-assembled into spherical nanoparticles capable of encapsulating IND at high loading capacity and loading efficiency. Differential scanning calorimetry and X-ray diffraction measurements indicated that IND was molecularly or amorphously dispersed in the nanoparticles. Fourier transform infrared spectra revealed the presence of multiple intermolecular interactions, including hydrogen bonding, electrostatic forces, π–π stacking and hydrophobic interactions, between the block copolymer and the IND molecules. IND-loaded nanoparticles exhibited fast release under intestinal pH. Compared with raw IND, the utilization of PEI -g- PZLL as a carrier significantly enhanced the oral bioavailability of IND and improved its protective effect on renal ischemia-reperfusion injury, as evidenced by in vivo pharmacokinetic and pharmacodynamic studies. Cytotoxicity assay, histological observation and cellular uptake study suggested that PEI- g -PZLL was fairly biocompatible. All these results indicated that star-block copolymers PEI -g- PZLL could be used as efficient nanocarriers for IND and other poorly water-soluble drugs. Statement of Significance: The use of polyethylenimine (PEI) as an oral drug delivery carrier is limited because it is not biodegradable and the use of higher molecular weight PEI leads to improved efficiency but also increased cytotoxicity. The design of functionalized PEIs with low cytotoxicity and high efficiency is crucial for developing a successful oral drug delivery system. In our study, poly(ε-benzyloxycarbonyl-L -lysine) (PZLL)-grafted branched PEI (PEI- g -PZLL) was reported as an oral nanocarrier for indomethacin (IND). The low cytotoxicity and biodegradability, well-defined self-assembled nano-sized polymeric micelles, high loading capacity and loading efficiency, amorphous state of the encapsulated IND, as well as the enhanced oral bioavailability of IND, makes the copolymer PEI- g -PZLL a promising nanocarrier for the oral administration of IND and possibly other poorly water-soluble drugs.